2014
DOI: 10.1111/cdev.12216
|View full text |Cite
|
Sign up to set email alerts
|

Transactional Links Between Teacher–Child Relationship Quality and Perceived Versus Sociometric Popularity: A Three‐Wave Longitudinal Study

Abstract: This study examined how peer relationships (i.e., sociometric and perceived popularity) and teacher-child relationships (i.e., support and conflict) impact one another throughout late childhood. The sample included 586 children (46% boys), followed annually from Grades 4 to 6 (M(age.wave1) = 9.26 years). Autoregressive cross-lagged modeling was applied. Results stress the importance of peer relationships in shaping teacher-child relationships and vice versa. Higher sociometric popularity predicted more teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 79 publications
9
85
5
1
Order By: Relevance
“…However, this result was not confirmed in a study by Leflot et al (2011). Interestingly, effects of peers on teachers are shown to be stronger and more consistent than the reverse effect of teachers on peers (Mercer and DeRosier 2008;De Laet et al 2014). More consistent findings showed that peer rejection reduced the support children received from teachers 2 to 3 years later (De Laet et al 2014;Hughes and Chen 2011;Leflot et al 2011;Mercer and DeRosier 2008).…”
Section: Indirect Effects On Disobedience: Links Between Social Classmentioning
confidence: 79%
See 3 more Smart Citations
“…However, this result was not confirmed in a study by Leflot et al (2011). Interestingly, effects of peers on teachers are shown to be stronger and more consistent than the reverse effect of teachers on peers (Mercer and DeRosier 2008;De Laet et al 2014). More consistent findings showed that peer rejection reduced the support children received from teachers 2 to 3 years later (De Laet et al 2014;Hughes and Chen 2011;Leflot et al 2011;Mercer and DeRosier 2008).…”
Section: Indirect Effects On Disobedience: Links Between Social Classmentioning
confidence: 79%
“…A possible explanation for the impact of the teacher-child on peer relationships comes from social referencing theory (Hughes et al 2001), which presumes that the teacher serves as a social referent for children, thereby allowing classmates to make inferences about children's likability based on their observations of teacherchild interactions. It has indeed been found that receiving more teacher support increased the likelihood of later higher appraisal by peers (Hughes and Chen 2011;De Laet et al 2014;Mercer and DeRosier 2008). However, this result was not confirmed in a study by Leflot et al (2011).…”
Section: Indirect Effects On Disobedience: Links Between Social Classmentioning
confidence: 87%
See 2 more Smart Citations
“…Alguns estudos, embora em número menor (Laet et al, 2014), sugerem haver a influência inversa, ou seja, que a relação estabelecida com os pares pode interferir nas interações vivenciadas pelos alunos com seus professores. Pesquisas indicam que a rejeição pelos pares prediz a baixa preferência do professor, predição esta que pode ser mais forte do que a predição da rejeição pelos pares a partir da baixa preferência do professor (Hughes & Chen, 2011;Mercer & DeRosier, 2008).…”
Section: Representando a Preocupação Do Governo Com O Desenvolvimentounclassified